Images of Corporeality in Law: The Experience of the BRICS Countries - А. Zorina; I. Yapryntsev (BRICS Law Journal)
This article presents the authors’ approaches to understanding the concept of corporeality in its normative dimension. The purpose of the study is to conceptualize the images of human corporeality that exist in the system of legal regulation. Based on the idea that the research category is a representation of certain characteristics of the human body, the authors substantiate the possibility of using institutional and functional-activity approaches to analyzing human corporeality. Both of these approaches are based on distinct foundations, which include social institutions, fields of activity and functional purposes of the human body. The common basis for the two approaches lies in the biosocial component, which is considered one of the defining characteristics of an image of corporeality. Depending on the approach used, the authors propose three classifications of images of corporeality: private and public, collective and individual and normal and abnormal. Regulatory practices that are aimed at consolidating these images of corporeality are analyzed within the framework of the current legal regulations in the BRICS countries. The authors conclude by noting that corporeality is a biosocial category that serves as the basis for legal subjectivity, while gaps in existing images of corporeality are the basis for its normalization.